Physical Model Test on the Deformation Mechanism of Reservoir Bank Slopes With Sand Layers Under Coupled Hydro-Mechanical Conditions - Zhu, Junhua; Lv, Qing; Xie, Dian; Zeng, Runzhong; Wang, Ning; Qiao, Jianwei; Cai, Weibin (Frontiers in Earth Science, 2022)
The reservoir area is mostly located in the canyon area, and the geological structure is complex. There are a large number of unstable slopes on the bank of the reservoir. The stability of the slope is greatly affected by water storage and reservoir water regulation. In addition, sudden rainstorm and other external factors are prone to instability and failure. In this paper, the physical model test is used to study the seepage field and deformation characteristics of typical reservoir bank slopes with sand layer under different rainfall intensities, different water level fluctuation rates and their coupling effects. The results show that the responsiveness of pore water pressure inside the slope lags behind both water level fluctuation and rainfall. The lag time is inversely proportional to water level fluctuation rates under the single water level fluctuation condition, while it is proportional to water level fluctuation rates in the water level decline stage under the coupling effect condition. The rapid impoundment of reservoir area has a strengthening effect on the stability of reservoir bank slope. However, the accelerated deformation of slope occurs in the stage of water level decline, and the deformation rate is proportional to the water level fluctuation rates.